Balancing Consumer Protection and Industrial Growth: The Policy Dilemma of TVET Factory Product in Indonesia - Sari, Norma; Muchlas, Muchlas; Wisnujati, Andika (Journal of Vocational Education Studies, 2025)
The Teaching Factory (TeFa), as an integral component of the Technical and Vocational Education and Training (TVET) framework in Indonesian Vocational High Schools (SMK), has emerged as a crucial technique to align educational outcomes with industrial requirements.  Students receive training in technical skills as well as entrepreneurial and manufacturing processes through practical production activities.  This integration presents a policy issue when TeFa goods enter the market and confront industry standards and consumer protection legislation.  This study investigates three primary inquiries: (1) to what degree do TVET Factory products manufactured by SMKs in Indonesia adhere to relevant industry standards; (2) is the existing legal framework sufficient to ensure consumer protection concerning TeFa products; and (3) how should forthcoming policies and regulations be formulated to harmonize consumer protection with industry development goals in the execution of the TVET Factory program.  The research used a qualitative methodology, incorporating case studies from five vocational schools across diverse domains of expertise, augmented by interviews with stakeholders including educators, industry partners, and regulatory bodies.  The findings indicate that the compliance of TeFa products with industry standards remains inconsistent, and current rules do not specifically address items based on vocational education.  This generates legal uncertainty and impediments in product down streaming.  Consequently, a novel, adaptable policy framework is required to safeguard consumers while promoting industry expansion through the synergy of TVET and market laws.